Implementation of Pre-aqil Baligh (Before Puberty) Education Through “The Male and Female Programs” as an Effort to Form Religious Attitudes at Elementary School - Juwita, Sri; Fikri, Ahmad; Harisah; Diana, Rahmi; Witro, Doli (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2024)
This study aims to determine the implementation of pre-aqil baligh (before puberty) education through male and female programs as an effort to form students’ religious attitudes. Pre-aqil baligh education is essential to implement in elementary schools considering the development of puberty is faster. This research was conducted at Ashfiya Elementary School, which is one of the Islamic schools in the city of Bandung. The research subjects were fifth and sixth-grade students when they were closer to pre-aqil baligh. The method used is qualitative research, which is conducted in the form of case studies. The sources used in the research are observation and interviews. And supported by scientific articles (journals) and books related to research. Data collection techniques are carried out by reduction, presentation, and verification. The research found that pre-aqil baligh education can be implemented by providing education about morals, fiqh of haidh (menstruation) and ihtilam (wet dreams), early sex education, and the habit of reciting the Koran. This activity uses the mentoring method as an approach to students. The religious attitude that is formed from pre-aqil baligh education through the male and female programs consists of three religious dimensions, namely aqidah, sharia, and morals. (Penelitian ini bertujuan untuk mengetahui pelaksanaan pendidikan pra aqil baligh (sebelum pubertas) melalui “program laki-laki dan perempuan” sebagai upaya membentuk sikap religius peserta didik. Pendidikan pra-aqil baligh penting dilaksanakan di sekolah dasar mengingat perkembangan masa pubertas lebih cepat. Penelitian ini dilakukan di SD Ashfiya yang merupakan salah satu sekolah Islam di kota Bandung. Subyek penelitiannya adalah siswa kelas V dan VI yang mendekati pra aqil baligh. Metode yang digunakan adalah penelitian kualitatif dengan melakukan penelitian lapangan berupa studi kasus. Sumber yang digunakan dalam penelitian adalah observasi dan wawancara. Serta didukung dengan artikel ilmiah (jurnal) dan buku-buku yang berkaitan dengan penelitian. Teknik pengumpulan data dilakukan dengan cara reduksi, penyajian, dan verifikasi. Penelitian ini menemukan bahwa pendidikan pra aqil baligh dapat dilaksanakan dengan memberikan pendidikan tentang akhlak, fiqh haidh (haid) dan ihtilam (mimpi basah), pendidikan seks sejak dini, dan kebiasaan mengaji. Kegiatan ini menggunakan metode pendampingan sebagai pendekatan kepada siswa. Sikap keagamaan yang terbentuk dari pendidikan pra-aqil baligh melalui “program laki-laki dan perempuan” terdiri dari tiga dimensi keagamaan, yaitu aqidah, syariah, dan akhlak.)